The electronic band structure of hexagonal silicon polytypes - Chizhova Anastasia; Nikolskaya Alena; Zaitseva Ekaterina; Konakov Anton (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
This work is devoted to calculations and an analysis of the electronic band structure (BS) for hexagonal (2H, 4H, 6H) and rhombohedral (9R, 15R, 21R) silicon polytypes using the empirical pseudopotential method (EPM). The calculation results for 3C, 2H and 4H have been in good agreement with experimental data. The data for 6H, 15R and 21R were obtained and analyzed for the first time. The BS for the 9R polytype calculated by EPM was almost identical to that obtained by the density functional theory method. This result indicates the possibility of using EPM for constructing BSs of various polytypes. The advantages of EPM over others were noted. The dependences of the widths of the direct and indirect energy gaps on the of crystal hexagonality degree were also studied. A partial “straightening” of the BS was established with increasing this degree of the objects.